PENGARUH PERSEPSI IKLIM KELAS TERHADAP KESEJAHTERAAN PSIKOLOGIS PADA MAHASISWA - Chandra Susanto; Amya Bunga Fathiyah (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
Research on perceived classroom climate and students’ psychological well-being in Indonesia remains limited, particularly in higher education contexts and in studies using a correlational-predictive design. This study aimed to examine perceived classroom climate as a predictor of students’ psychological well-being, without drawing experimental causal conclusions. This study employed a quantitative approach with a correlational-predictive design. The participants were 150 active undergraduate students selected through simple random sampling. Data were collected using a classroom climate scale adapted from the College and University Classroom Environment Inventory (CUCEI) and a psychological well-being scale adapted from Ryff’s Psychological Well-Being Scale (RPWB). Both instruments underwent expert validation and reliability testing, with results indicating that they were appropriate for use in research data collection. The data were analyzed using simple linear regression. The results showed that perceived classroom climate positively and significantly predicted students’ psychological well-being, F(1,148) = 76.541, p < .001, with R² = .341. This finding indicates that perceived classroom climate explained 34.1% of the variance in students’ psychological well-being. Thus, the more positive students’ perceptions of the classroom climate, the higher their tendency to experience psychological well-being. This study concludes that a supportive, inclusive, and psychologically safe classroom climate plays an important role in supporting students’ well-being. The practical implication of this study highlights the need to strengthen lecturers’ competencies in building supportive classroom interactions, providing constructive feedback, and creating learning environments that are responsive to students’ psychological needs in higher education. ABSTRAK Penelitian mengenai persepsi iklim kelas dan kesejahteraan psikologis mahasiswa di Indonesia masih terbatas, terutama pada konteks pendidikan tinggi dan penggunaan desain korelasional-prediktif. Penelitian ini bertujuan untuk menguji persepsi iklim kelas sebagai prediktor kesejahteraan psikologis mahasiswa, tanpa menarik kesimpulan kausal secara eksperimental. Penelitian ini menggunakan pendekatan kuantitatif dengan desain korelasional-prediktif. Partisipan terdiri atas 150 mahasiswa aktif tingkat sarjana yang dipilih melalui teknik simple random sampling. Data dikumpulkan menggunakan skala iklim kelas yang diadaptasi dari College and University Classroom Environment Inventory (CUCEI) dan skala kesejahteraan psikologis yang diadaptasi dari Ryff’s Psychological Well-Being Scale (RPWB). Kedua instrumen telah melalui validasi ahli dan uji reliabilitas, dengan hasil yang menunjukkan kelayakan instrumen untuk digunakan dalam pengumpulan data penelitian. Data dianalisis menggunakan regresi linear sederhana. Hasil penelitian menunjukkan bahwa persepsi iklim kelas secara positif dan signifikan memprediksi kesejahteraan psikologis mahasiswa, F (1,148) = 76,541, p < 0,001, dengan R² = 0,341. Temuan ini menunjukkan bahwa persepsi iklim kelas menjelaskan 34,1% varians kesejahteraan psikologis mahasiswa. Dengan demikian, semakin positif persepsi mahasiswa terhadap iklim kelas, semakin tinggi kecenderungan kesejahteraan psikologis yang dimiliki. Penelitian ini menyimpulkan bahwa iklim kelas yang suportif, inklusif, dan aman secara psikologis berperan penting dalam mendukung kesejahteraan mahasiswa. Implikasi praktis penelitian ini menekankan perlunya penguatan kompetensi dosen dalam membangun interaksi kelas yang suportif, memberikan umpan balik konstruktif, dan menciptakan lingkungan belajar yang responsif terhadap kebutuhan psikologis mahasiswa di perguruan tinggi.